(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study investigates the chemical composition and nutritional value of feed additives (Vilofoss, Likra, and Profat) used in dairy cow rations. Laboratory analyses were conducted at the State Scientific Center for Quality and Circulation Control of Veterinary Drugs and Feed Additives under the Veterinary and Livestock Development Committee of the Republic of Uzbekistan. Based on the primary chemical analysis results, the nutrient content and metabolizable energy of feeds and feed additives were calculated and balanced rations were formulated. The metabolizable energy (ME) values were determined according to the 2008 All-Russian Research Institute of Animal Husbandry guidelines using standardized equations depending on feed type. Energy values were expressed in International System (SI) units (MJ) and converted into Energy Feed Units (EFU), where 1 EFU equals 10 MJ of metabolizable energy. The results showed that all analyzed feeds met zootechnical and veterinary requirements in terms of chemical composition and energy value. Nitrogen-free extract substances constituted 51,5-81,4% of the total metabolizable energy. The average nutritional values (EFU) of the main feeds were: alfalfa hay - 0,71; corn silage - 0,21; fodder beet - 0,08; alfalfa haylage - 0,36; wheat straw - 0,66; wheat grain - 1,06; barley grain - 0,97; compound feed (BDK) - 0,97 EFU. The obtained results confirm that determining feed nutritional value based on primary laboratory chemical analysis provides more accurate and scientifically substantiated ration formulation for dairy cattle.